Energy transport analysis in natural convective flow of water:Ethylene glycol (50:50)-based nanofluid around a spinning down-pointing vertical cone - Iqbal, Zahoor; Yashodha, S.; Hakeem, A. K. Abdul; Alsawi, Abdulrahman; Alyami, Maryam Ahmed; Yousef, El. Sayed; Amin, Ali H.; Eldin, Sayed M. (Frontiers in Materials, 2022)
This article is prepared by using Tiwari-Das nanofluid model. The Influence of the magnetic field on H_2 O-C_2 H_6 O_2 (50:50) based nanofluid over a heated and spinning vertical cone is deliberated. Water-Ethylene Glycol (50:50) mixture based nanofluid with 〖Al〗_2 O_3 and 〖Fe〗_3 O_4 as nanoparticles exhibit higher thermal conductivity enhancement. Heat transfer analysis for the spinning vertical cone with prescribed surface temperature is investigated. The influence of magnetic parameter, spin parameter and other physical parameters on nanoparticle volume fraction profile, tangential velocity profile, spin velocity profile, and on thermal profile is analyzed. The results demonstrate strong accordance with the findings of previous research works in the special cases. Our computation shows that as M increases, metallic nanoparticles exhibit higher velocity compared to the non-metallic nanoparticle in the presence of H_2 O-C_2 H_6 O_2 (50:50) mixture.